2005
DOI: 10.1002/hed.20146
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal cancer patients: Analysis of patient delay at different tumor stages

Abstract: Patient delay was significantly longer in cases of glottic cancer, but diagnosis at an early stage of the disease was more frequent among these patients than among patients with supraglottic cancer. Advanced supraglottic cancer probably has a late onset of symptoms. Thus, earlier intervention will probably not result in a significantly higher proportion of small supraglottic cancers being diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 18 publications
4
70
0
Order By: Relevance
“…Several studies indicate that the worsening and progression of symptoms is a main factor prompting consultation in primary care, 10,27,32,34 and in many cases the patient attributed these symptoms to mild benign illness. 27,34 In addition, the propensity to seek help for health-related matters varies across people, 43 which likely explains some of the patientrelated delay that has been observed, and health-related lay social networks can vary in quality, thereby influencing a patient's decision to seek a professional opinion about symptoms. 44 The practice of studying populations of patients whose cancers are from across the spectrum of head and neck sites likely undermines the ability to observe an association between diagnostic delay and stage, as symptoms and tumor biology vary among these sites.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies indicate that the worsening and progression of symptoms is a main factor prompting consultation in primary care, 10,27,32,34 and in many cases the patient attributed these symptoms to mild benign illness. 27,34 In addition, the propensity to seek help for health-related matters varies across people, 43 which likely explains some of the patientrelated delay that has been observed, and health-related lay social networks can vary in quality, thereby influencing a patient's decision to seek a professional opinion about symptoms. 44 The practice of studying populations of patients whose cancers are from across the spectrum of head and neck sites likely undermines the ability to observe an association between diagnostic delay and stage, as symptoms and tumor biology vary among these sites.…”
Section: Discussionmentioning
confidence: 98%
“…Provider delay Teppo et al 33 ; Brouha et al 34 *Relationship suggested only; no statistical testing done or relationship only approached significance (P < .10).…”
Section: Patient Delaymentioning
confidence: 96%
See 1 more Smart Citation
“…As a result, all patients were diagnosed with an advanced stage of the disease accompanied by enlarged lymph nodes in the neck. The misinterpretation of cancer symptoms is a problem that has been reported elsewhere [24, 25]. Additionally, patients were not aware of the consequences of a delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…4 There are both benign and malignant factors that can cause dysphonia, but what is concerning is that up to 52% of patients with laryngeal cancer thought their hoarseness was harmless, leading to a delay in evaluation and treatment. 5 The guidelines list comorbidities that should trigger a patient and clinician to suspect a serious underlying cause of the dysphonia (Box 1). This article builds on the invaluable article by Blitzer, elsewhere in this issue, regarding laryngeal anatomy and function, and presents a laryngologist's focus on the different tools, highlights, and pitfalls in the evaluation of the dysphonic patient.…”
mentioning
confidence: 99%